Official 1991 Blackbook Price Guide of United States Paper Money - Hudgeons, Marc. (New York House of Collectibles, 1991)
The Official Blackbook Price Guide of United States Paper Money is designer as a reference aid for collectors, dealers, and the general public. Its purpose is to provide historical and collecting data, as well as current values.
Keywords: Economics